Posouzení informačního systému firmy a návrh změn - Stuchlíková, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zabývá posouzením procesu provádění nedestruktivních kontrol firmy ČEZ, a. s. v divizi Jaderná energetika a návrhem změn pro tento proces a zapojených informačních systémů. První část diplomové práce definuje základní pojmy a teoretická východiska. Druhá část obsahuje analýzu současného stavu procesu provádění nedestruktivních kontrol a příslušných systémů, které jsou v procesu zapojeny. Třetí část obsahuje návrh na zlepšení analyzovaného procesu, další návrhy a ekonomické zhodnocení návrhů.

This diploma thesis deals with the evaluation of the process of performing non-destructive testing in the Nuclear energy division of the ČEZ, a. s. and the design of changes for this process and the information systems involved. The first part of the diploma thesis defines the basic terminology and the theoretical basis for further use. The second part includes an analysis of the current state of the process of performing non-destructive testing and the relevant systems that are involved in the process. The third part contains a proposal to improve the process of conducting non-destructive testing, further proposals, and economic evaluation of proposals
Information System Assessment and Proposal of ICT Modification
Keywords: data; informace; informační systém; proces; ZEFIS; PEST; 7S; NDT; data; information; information system; process; ZEFIS; PEST; 7S; NDT